Full-Scale Dynamic Testing of a Sliding Seismically Isolated Unibody House. Issue 4 (November 2016) - Jampole, Ezra; Deierlein, Gregory; Miranda, Eduardo; Fell, Benjamin; Swensen, Scott; Acevedo, Cristian
Shaking table tests were conducted on a new low cost sliding seismic isolation system aimed at significantly improving the seismic performance of low-rise lightweight residential construction. A two-story, full-scale seismically isolated wood frame house was tested dynamically under multiple ground motions on a shake table. Two different sliding isolation bearings were evaluated, one with flat and another with concave sliding surfaces, both with high-density polyethylene sliders on galvanized steel surfaces with a coefficient of friction of approximately 0.18. Each isolation system was subjected to seven severe recorded earthquake ground motions, which produced peak isolator displacements of up to 41 cm. The maximum induced inertial shear force on the superstructure was on the order of 0.4 g, yet the house remained practically damage-free with story drift ratios less than 0.1%. The study successfully (1) provides a proof-of-concept for design, construction, and behavior of a light-frame house with low-cost high friction sliding seismic isolation, (2) confirms several design assumptions regarding isolation behavior and maximum isolation displacement, and (3) provides data to validate computational models and develop design guidelines for the isolated superstructure.